2023
DOI: 10.1051/0004-6361/202245042
|View full text |Cite
|
Sign up to set email alerts
|

Euclid preparation

Abstract: The various Euclid imaging surveys will become a reference for studies of galaxy morphology by delivering imaging over an unprecedented area of 15 000 square degrees with high spatial resolution. In order to understand the capabilities of measuring morphologies from Euclid-detected galaxies and to help implement measurements in the pipeline of the Organisational Unit MER of the Euclid Science Ground Segment, we have conducted the Euclid Morphology Challenge, which we present in two papers. While the companion … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 50 publications
0
6
0
1
Order By: Relevance
“…As we move into the hidden layers, this scaling issue only gets worse. Also, since MLPs must take an unrolled image as an input, they disregard any spatial properties of their training images, and so either need a substantial amount of training data to classify or generate large images, 12 or an expert to extract descriptive features from the data in a preprocessing step. We can see this issue writ large in the previous section-most of the MLP applications described in §3 require an expert to extract features from the data for the network to then train on!…”
Section: Contemporary Supervised Deep Learningmentioning
confidence: 99%
See 2 more Smart Citations
“…As we move into the hidden layers, this scaling issue only gets worse. Also, since MLPs must take an unrolled image as an input, they disregard any spatial properties of their training images, and so either need a substantial amount of training data to classify or generate large images, 12 or an expert to extract descriptive features from the data in a preprocessing step. We can see this issue writ large in the previous section-most of the MLP applications described in §3 require an expert to extract features from the data for the network to then train on!…”
Section: Contemporary Supervised Deep Learningmentioning
confidence: 99%
“…Fussell & Moews [229] achieved this with a stacked GAN architecture [231], and Holzschuh et al [230] use the related StyleGAN architecture [189] to the same end. Bretonnière et al [12] use a flow-based model 36 [233,234] to conditionally simulate galaxy observations. They found that their approach could produce more accurate simulations than the previous analytical approach, at the cost of inference time.…”
Section: Deep Astronomical Generative Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of publications have demonstrated a diverse set of applications for an ab initio simulator in astronomy using PhoSim 1 . PhoSim has been used to (1) to test the design of Rubin/LSST (Xin et al 2015;Angeli et al 2016;Thomas et al 2016) and JWST , (2) to plan for future observations (e.g., Chang et al 2012Chang et al , 2013aChang et al , 2013bBard et al 2013Bard et al , 2016Mandelbaum et al 2014;Thomas & Kahn 2018;Sanchez et al 2020;Bretonniere et al 2023;Merlin et al 2023), (3) for advanced image processing algorithm development (e.g., Meyers & Burchat 2015;Li et al 2016;Carlsten et al 2018;Nie et al 2021aNie et al , 2021b, (4) to understand physical effects (Beamer et al 2015;Xin et al 2018;Walter 2015), and (5) for advanced AI/machine learning development by simulating training sets ). In addition to published studies, hundreds of users have used PhoSim for informal studies.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of Euclid data alone, 30 out of the 65 contaminants cannot be included in these diagrams because they do not have a well-constrained (I E − Y E ) colour. 4, this means that in the worst-case scenario, 30 additional contaminants could actually survive this selection, and so the contamination fraction would be 0.11 instead of 0.01. Therefore, the purity of the apparent z > 6 sample would still improve from applying colour selection criteria, although possibly not as drastically as presented in Table 2.4.…”
Section: Colour Cutmentioning
confidence: 99%